Prospects for the Use of Donor Blood in a Cardiac Surgery Clinic - B. N. Gumeniuk; V. L. Dyachenko; M. V. Dyachenko; S. A. Kalashnikov (Ukrainian Journal of Cardiovascular Surgery, 2020)
Investigation of problems of infection among patients with heart diseaseand blood donors, diagnosisand detection of serological markers of hepatitis B, C, syphilis, HIV infection and alternative development of free donation.The aim. To analyze the dynamics of serotypes of infections in patients and donors in recent years, and to determine the prospects of free donation in a cardiac surgery clinic.Materials and methods. The study was performed by means of detection of hepatitis B, hepatitis C, syphilis and HIV infection markers in 19,965 patients with heart diseases and 9,502 donors in 2017-2019, and included analysis of the development of voluntary blood donation in Ukraine.Results. In 2017-2019, a 4-fold increase in the total amount of donated blood was noted due to the development of Voluntary Blood Donation (VBD) program. In patients with heart diseases requiring surgical treatment, the average rate of infection in this period was 5.76%. Among blood donors in those years, there was a notable increase in serological markers of syphilis (5.3-fold) and HIV infection (2.3-fold). In the process of examination and procurement of donated blood, the lack of donor blood from relatives of patients is 27%, and the lack of blood from voluntary donors is 17%.Conclusion. Increase in the amount of donated blood thanks to the first-time donors in the VBD program requires careful laboratory monitoring to detect antibodies to the causative agents of syphilis, hepatitis B, C and HIV, as well as mandatory post-quarantine laboratory monitoring of donor plasma.